2016
DOI: 10.17795/minsurgery-35609
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Tapp Inguinal Hernia Repair: Mesh Fixation With Absorbable Tacks, Initial Experience

Abstract: Background: Preliminary studies have indicated advantages of mesh fixation using fibrin glue in TAPP compared with tack fixation. Objectives: We report the results of a prospective experience in fixing mesh during TAPP with absorbable tacks. Patients and Methods: 50 consecutive men (who had bilateral inguinal hernia) were enrolled and followed up for at least 1 year. The primary measured outcome was pain experienced in day 1 of post-op. The secondary outcomes measured were postoperative scores of pain at rest,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…The mean number of tacks was 16.87±3.22 in group A and 19 (13)(14)(15)(16)(17)(18)(19)(20) with mean 17.4±2.92 in group B. This is comparable with other studies.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The mean number of tacks was 16.87±3.22 in group A and 19 (13)(14)(15)(16)(17)(18)(19)(20) with mean 17.4±2.92 in group B. This is comparable with other studies.…”
Section: Discussionsupporting
confidence: 88%
“…This is comparable to the results of Agresta et al study. 13 The postoperative pain assessment results in this study are comparable to other studies. In a multicenter study assessing the use of absorbable tacks as regard postoperative pain revealed that at 1 month, 90% of patients were totally pain-free (VAS score: 0) and only ten patients reported low pain (VAS scores: 0.3-3.1).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations